Upgrading process in global value chains: Evidence from Latin American countries - Rivera-Basques, Luisa (Technium Social Sciences Journal, 2022)
This paper analyzes the participation of Argentina, Brazil, Chile, Colombia, Costa Rica, Mexico, and Peru (Latin American countries) in Global Value Chains (GVCs) from a multi-regional and multi-sectoral perspective in the period 1995-2015. Our objective is to answer a key question: the participation of Latin American countries in GVCs, in which sectors and industries have they evolved towards upgrading processes? We use a multi-regional in-put-output model (MRIO) to estimate domestic and foreign value-added rates as a percentage of total national exports, classifying the participation of the countries in GVCs into four pro-duction stages: strategic, intermediate-final stages, initial and secondary. We find that GVCs have been drivers of the development of the manufacturing industry in Mexico, Brazil, Argentina, and Costa Rica. Upgrading processes stand out in value-added intensive industries, such as the manufacture of vehicles, trailers and semi-trailers, electronic, electrical, and optical products, among others.